HUBUNGAN KEPRIBADIAN DAN SIKAP SOSIAL PESERTA DIDIK TERHADAP PRESTASI BELAJAR AKIDAH AKHLAK - Yanti Mala Yulidar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The study achievement in Akidah Akhlak has contributed in giving motivation to the students to learn and practice the aqidah in the form of habit in doing good moral and attitude and also avoiding the bad moral in the daily life of privacy, social and nationality life. The study achievement is influenced by internal and external factors, such as personality and social attitude. This research purpose was to know the relationship between personality and the students’ social attitude with the study of Akidah Akhlak in the first semester. This research used a correlational quantitative approach. The research variables consist of independent and dependent variables. The independent variables are personality and social attitude (x), while the dependent variable is the study achievement of Akidah Akhlak (Y). The subject is 67 students of MTs Tsanawiyah Al Hidayah. The research instrument was closed questionnaires for personality variables and social attitude, also the result of achievement of Akidah Akhlak lesson in the first semester. The data analysis used the product-moment Pearson’s correlational technique. The result of the research showed that personality and social attitude had a significant positive relationship towards the study achievement of Akidah Akhlak with the correlation value = 0,519.